Redox transitions between oxygen intermediates in cytochrome-c oxidase. - Verkhovsky, M I (1996)
Some intermediates in the reduction of O2 to water by cytochrome-c oxidase have been characterized by optical, Raman, and magnetic circular dichroism spectroscopy. The so-called "peroxy" (P) and "ferryl" (F) forms of the enzyme, which have been considered to be intermediates of the oxygen reaction, can be generated when the oxidized enzyme reacts with H2O2, or when the two-electron reduced ("CO mixed-valence") enzyme reacts with O2. The structures as well as the overall redox states of P and F have recently been controversial. We show here, using tris(2,2'-bipyridyl)ruthenium(II) as a photoinducible reductant, that one-electron reduction of P yields F, and that one-electron reduction of F yields the oxidized enzyme. This confirms that the overall redox states of P and F differ from the oxidized enzyme by two and one electron equivalents, respectively. The structures of the P and F states are discussed.